2017
DOI: 10.1016/j.acra.2016.08.025
|View full text |Cite
|
Sign up to set email alerts
|

A New Contrast Enhancement Protocol for Subtraction Coronary Computed Tomography Requiring a Short Breath-Holding Time

Abstract: Rationale and Objectives:We have developed a new contrast enhancement protocol for subtraction coronary computed tomography (SCCTA) requiring a short breath-holding time. In the protocol, test and main boluses were sequentially and automatically injected, and correct timings for pre-contrast and contrast-enhanced scans for main bolus were automatically determined only by the test bolus tracking. Combined with a fixed short main bolus injection for 7 seconds, the breath-holding time was shortened as possible. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The main bolus injection for 7 seconds was automatically started, followed by injection of a saline solution for 7 seconds. [ 12 , 13 ] The iodine contrast medium (370 mgI/mL, iopamidol 370, Bayer AG, Germany) was injected via antecubital vein at a rate of body weight (kg) × 0.07, the total amount of main bolus injection injected was weight (kg) × 0.49–0.7 mL. After the injection of contrast medium, 40 mL of normal saline solution was immediately flushed at the same rate.…”
Section: Methodsmentioning
confidence: 99%
“…The main bolus injection for 7 seconds was automatically started, followed by injection of a saline solution for 7 seconds. [ 12 , 13 ] The iodine contrast medium (370 mgI/mL, iopamidol 370, Bayer AG, Germany) was injected via antecubital vein at a rate of body weight (kg) × 0.07, the total amount of main bolus injection injected was weight (kg) × 0.49–0.7 mL. After the injection of contrast medium, 40 mL of normal saline solution was immediately flushed at the same rate.…”
Section: Methodsmentioning
confidence: 99%
“…The feasibility of subtraction CCTA has been verified by several studies, and subtraction CCTA allows for a significant improvement in diagnostic accuracy owing to its higher specificity and positive predictive value for the assessment of coronary artery stenosis than those of conventional CCTA alone (103)(104)(105)(106)(107)(108)(109). However, the proportion of segments excluded because of misregistration is still high even in the most recently published study, which reported misregistration in approximately half (53%) of all target segments (109).…”
Section: Challenging Techniques In Cardiothoracic Imaging: Free-breathing Scans and Subtraction Imagingmentioning
confidence: 97%
“…Manual correction can be considered in case of significant lesions, but it is highly time-consuming. Moreover, although the breath-holding times of this single breath-hold method have been shortened to approximately 15–18 seconds, this breath-holding time remains problematic in some patients (107108). In highly selected patients for whom CCTA can be challenging because of an extensive calcium load or inability to tolerate breath-holding, with successful registration, subtraction CCTA may be helpful in the current technique.…”
Section: Applications Of Wide-detector Ct In Cardiothoracic Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The examination was performed using a 256-row detector CT system (Revolution CT; GE Healthcare, Milwaukee, WI, USA) using the test bolus tracking method. 1 First, the test bolus was injected for 2 s, followed by a 0.9% saline solution for another 4 s. Then, after waiting for 20 s, the main bolus injection for 18 s was automatically started, followed by the injection of a saline solution for 4 s. The CT operator then manually pressed the acquisition trigger button at the beginning of the enhancement of the right ventricle in the test bolus (the trigger point), visually assessing the monitor images along with the enhancement curve measured in the region of interest (ROI) placed on the right ventricle. After the subsequent scan delay of 23 s from the trigger point, an intermittent image acquisition was automatically started.…”
Section: Case Descriptionmentioning
confidence: 99%